A novel CARD14 variant, homozygous c.526G>C (p.Asp176His), in an adolescent Japanese patient with palmoplantar pustulosis. (5th February 2019) - Tobita, R.; Egusa, C.; Maeda, T.; Abe, N.; Sakai, N.; Suzuki, S.; Kawashima, H.; Hokibara, S.; Ko, J.; Okubo, Y.
Abstract : Click here for the corresponding questions to this CME article.